BASIC JAPANESE UNTUK AKTIFITAS PROMOSI WISATA BAGI PELAKU USAHA WISATA DI DESA KANDRI, SEMARANG - Sri Wahyu Istana Trahutami; Reny Wiyatasari (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Kandri is a tourist village located in the sub-district of Gunung Pati, Semarang. This village has a lot of natural potential and cultural wealth that can be developed for tourism. Community Service activities are carried out through training followed by tour guides and tourism business service actors in Kandri Village, Semarang. Due to the pandemic, activities were carried out with a limited number of participants and strict health protocols were followed. Basic Japanese training is focused on the practical purposes of making travel promotions. The training continues until the trainees can independently create tourism promotional content and upload it on social media. This activity is running smoothly, and the participants are very enthusiastic about participating in the training. Community service partners are satisfied with the implementation of activities and hope that there will be a continuation of community service activities. Keywords: tourism, tour guide, optimization, socialization, tourism village